The assessment of the correlation between vascular endothelial growth factor (VEGF), tumor necrosis factor (TNF-α), interleukin 6 (IL-6), glycaemic control (HbA1c) and the development of the diabetic retinopathy in children with diabetes mellitus type 1 - Myśliwiec, Małgorzata; Balcerska, Anna; Zorena, Katarzyna; Myśliwska, Jolanta; Lipowski, Paweł; Raczyńska, Krystyna (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
The aim of the work is to assess the correlation between HbA1c, VEGF, TNF-α, IL-6 and the development of diabetic retinopathy in children diagnosed with diabetes mellitus type 1. One hundred fourty nine children with long-standing diabetes mellitus type 1 were enrolled in the study. The patients were divided into two subgroups: children with retinopathy (Group 1; n=28) and children without retinopathy (Group 2, n=121). The control group consisted of 62 healthy children. All the examined children had VEGF, TNF-α and IL-6 measured in the blood serum using highly sensitive ELISA tests. Statistically significant higher blood serum levels of HbA1c, VEGF, TNF-α and IL-6 were found in the group 1 in comparison with the group 2. Children of the group 2 in relation to healthy controls showed statistically significant higher blood serum levels of VEGF, TNF-α and IL-6. Elevated levels of VEGF, TNF-α, IL-6, HbA1c in blood serum of children with diabetes mellitus type 1 detected before development of overt signs of diabetic retinopathy might indicate the possibility of the occurrence of changes in the eye shortly.